2004
DOI: 10.1016/j.jcrs.2003.12.035
|View full text |Cite
|
Sign up to set email alerts
|

Measuring rectilinear flow within the anterior chamber in phacoemulsification procedures

Abstract: Peak vibration velocity and amplitude of displacement were less with the WhiteStar delivery modes than with continuous power or short-pulse modes. A similar reduction was seen in the rectilinear flow under Schlieren photography. Attenuation of rectilinear flow and turbulence patterns may have clinical implications for the corneal endothelium during phacoemulsification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
2

Year Published

2006
2006
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 5 publications
0
5
0
2
Order By: Relevance
“…Steinert and Schafer [4] used the Doppler method to measure the planar velocity distribution of irrigation fluid flow near the handpiece tip; they observed fluid movement, produced by a nonlinear effect known as acoustic streaming, directly below the tip. Oki used the Schlieren method to visualize the flow near the tip and found that sonication causes rectilinear flow patterns [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Steinert and Schafer [4] used the Doppler method to measure the planar velocity distribution of irrigation fluid flow near the handpiece tip; they observed fluid movement, produced by a nonlinear effect known as acoustic streaming, directly below the tip. Oki used the Schlieren method to visualize the flow near the tip and found that sonication causes rectilinear flow patterns [5].…”
Section: Discussionmentioning
confidence: 99%
“…Third, only 2-dimensional images are obtained when video images are captured with a CCD camera positioned above the eye. Doppler techniques do not have the problems concerning particles; however, these techniques fail to measure the velocity distribution of irrigation fluid flow in every part of the anterior chamber [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…The results indicated there was fluid movement, which was produced by a nonlinear effect known as acoustic streaming, directly below the phacoemulsification tip. Oki (2004) used the schlieren method to visualize the flow near the tip and found that sonification caused rectilinear flow patterns. While the above studies clarified the detailed flow features near the phacoemulsification tip, studies of the actual flow field that occurs in the eye have not yet been published.…”
Section: Discussionmentioning
confidence: 99%
“…Nesta pesquisa, a média de perda percentual das células endoteliais, após três meses, foi semelhante em ambos os ciclos de ultra-som (9% para o ciclo 14% e 10% para o ciclo 67%). Esses resultados, provavelmente, podem ser explicados por outro na literatura (4) , que comparou a onda de pressão gerada pela ponteira da caneta de facoemulsificação em diferentes modulações de ultra-som, numa experiência de laboratório. O autor demonstrou que a modulação de micropulso (67% e 33% ultra-som ligado) apresentou menor onda de pressão do que no pulso curto (30% ultra-som ligado).…”
Section: Discussionunclassified
“…Esse melhor aproveitamento da energia ultra-sônica nos permite reduzir o tempo de ultra-som durante a cirurgia. É possível, ainda, modular o tempo de ultra-som ligado e desligado durante o procedimento, aproveitando ao máximo a sua eficiência, dependendo da fase da cirurgia (4) . Muitos pesquisadores têm relatado que a energia ultra-sôni-ca usada durante a facoemulsificação do núcleo continua sendo uma fonte de perda de células endoteliais e dano tecidual (5)(6)(7)(8) .…”
unclassified